Antimycobacterial activity of medicinal plants against the causative agent of buruli ulcer: Mycobacterium ulcerans. (December 2016) - Keumoe, R.; Nguembou, M.S.; Tsouh, F.P.V.; Donkeng, D.V.F.; Dize, D.; Tchokouaha, Y.L.R.; Jiatsa, M.C.D.; Youmsi, F.R.D.; Ngameni, B.; Fekam, B.F.
Abstract: Objective/background: Buruli ulcer, known as necrotizing skin disease caused by Mycobacterium ulcerans, has emerged as the most prevalent mycobacteriosis after leprosy and tuberculosis. Accordingly, it has been classified by the World Health Organization as a neglected disease with high significance in tropical areas, including Cameroon. So far, the control of the disease relies mainly on the rifampin-streptomycin combination. Despite its efficiency, it has shown considerable issues, including availability and side effects. Therefore, more effective and safer drugs are urgently warranted. For this fact, natural plant-based products have always been of great importance in drug discovery. Therefore, the present study was initiated to assess the antimycobacterial properties of four medicinal plants against M. ulcerans . Methods: The methanolic and aqueous crude extracts prepared from Ficus binjamina, Ficus elastica, Ficus saussureana, and Terminalia superba were screened against M. ulcerans using the resazurin microtiter assay method. The phytochemical screening of promising extracts was performed to reveal bioactive components that might explain the exhibited activity. Results: Out of the 24 tested extracts, 11 extracts showed promising activity with minimal inhibitory concentration ranging from 62.5 μg/mL to 250 μg/mL. The phytochemical screening revealed the presence of phenols, flavonoids, tanins, triterpenes, glucosides, and saponins. Conclusion: The obtained results further strengthened the exploitation of these extracts as potent hits in the treatment of Buruli ulcer. Meanwhile, further studies are required to fully characterize the bioactive compounds.